Plant secondary metabolite-induced shifts in bacterial community structure and degradative ability in contaminated soil - Uhlik, Ondrej; Musilova, Lucie; Ridl, Jakub; Hroudova, Miluse; Vlcek, Cestmir; Koubek, Jiri; Holeckova, Marcela; Mackova, Martina; Macek, Tomas (Applied microbiology and biotechnology, 2013)
The aim of the study was to investigate how selected natural compounds (naringin, caffeic acid, and limonene) induce shifts in both bacterial community structure and degradative activity in long-term polychlorinated biphenyl (PCB)-contaminated soil and how these changes correlate with changes in chlorobiphenyl degradation capacity. In order to address this issue, we have integrated analytical methods of determining PCB degradation with pyrosequencing of 16S rRNA gene tag-encoded amplicons and DNA-stable isotope probing (SIP). Our model system was set in laboratory microcosms with PCB-contaminated soil, which was enriched for 8 weeks with the suspensions of flavonoid naringin, terpene limonene, and phenolic caffeic acid. Our results show that application of selected plant secondary metabolites resulted in bacterial community structure far different from the control one (no natural compound amendment). The community in soil treated with caffeic acid is almost solely represented by Proteobacteria, Acidobacteria, and Verrucomicrobia (together over 99 %). Treatment with naringin resulted in an enrichment of Firmicutes to the exclusion of Acidobacteria and Verrucomicrobia. SIP was applied in order to identify populations actively participating in 4-chlorobiphenyl catabolism. We observed that naringin and limonene in soil foster mainly populations of Hydrogenophaga spp., caffeic acid Burkholderia spp. and Pseudoxanthomonas spp. None of these populations were detected among 4-chlorobiphenyl utilizers in non-amended soil. Similarly, the degradation of individual PCB congeners was influenced by the addition of different plant compounds. Residual content of PCBs was lowest after treating the soil with naringin. Addition of caffeic acid resulted in comparable decrease of total PCBs with non-amended soil; however, higher substituted congeners were more degraded after caffeic acid treatment compared to all other treatments. Finally, it appears that plant secondary metabolites have a strong effect on the bacterial community structure, activity, and associated degradative ability.
Keywords: Bacteria; sekundární metabolismus; polychlorované bifenyly; půdní mikrobiologie; Soil Pollutants; Secondary Metabolism; Soil; Biodegradation, Environmental; Soil Microbiology; biodegradace; rostliny; půda; Plants; Polychlorinated Biphenyls; látky znečišťující půdu